Особенности ультразвуковой диагностики пограничных опухолей яичников - Клименко, Э.С.; Головко, Т.С.; Бакай, О.А.; Свинцицкий, В.С. (Актуальні проблеми транспортної медицини, 2014)
Проведен анализ результатов ультазвукового обследования 847 больных опухолями яичников, из них 28 пограничными опухолями (ПОЯ). Полученные результаты свидетельствуют о достаточно благоприятном клиническом заболевания у больных ПОЯ I стадии, с начальным опухолевым процессом. Доказано, что сонография в
совокупности с допплерографией является надежным методом диагностики рецидива у больных ПОЯ. Був проведений аналіз результатів
ультразвукових обстежень 847 хворих пухлинами яєчників, з них 28 граничними пухлинами яєчників (ГПЯ). Отримані результати свідчать про досить сприятливий
клінічний перебіг захворювання у хворих
ГПЯ 1 стадії з початковим пухлинним процесом. Доказано, що сонографія в купі з
доплерографією є надійним методом діагностики рецидивів у хворих на ГПЯ. Actuality of the topic. Ovarian tumors occupies the third place in the structure of oncological diseases of women genitals, but the mortality occupies the first
place and makes 49 %. Epidemiological
investigations showed, that the vivid tendency for the growth of morbidity is indicated during the last decades, ovarian tumors are met in all age groups, beginning
from the early juvenile age up to senile,
more often the tumors are identified at
women of reproductive period, that’s why
the tumors represent not only medical
problem but also a social one.
Borderline ovarian tumors (BOT) occupies an important place among new formations of ovaries, so called carcinomas
with low potential of malignancy. According
to modern data, among all other ovarian
tumors, borderline forms make from 5 up
to 20 %. Nowadays in modern society and
modern facilities, transvaginal echography
is an obligatory method of diagnostics of
all women with suspicion for the presence
of tumor or tumoral formation of ovaries.
The aim of investigation. To study
the peculiar features of Ultra Sound Diagnostics of borderline ovarian tumors for the
working out of modern principles of prognosis of clinical flow and for working out of
treatment tactics for this category of patients.
Materials and methods. During a
period from 2006 up to 2011, according to
statistics, among the total amount of 847
patients with malignant epithelial, non epithelial ovarian tumors of I IV stages in the
Lugansk Regional Clinical Oncological
Dispensary(LRCOD) pure carcinomas were
diagnosed at 658(77,6 %) patients, non
epithelial malignant new formations – at
189 (19,9 %) cases, BOT were identified at
28 (3,3 %) patients. The age of the patients
with BOT varies from 20 up to 89 years old,
the average age is 44,7 ± 1,8 years old.
The results of investigation and
their discussion. With the aim of identification of the diagnostic value of echography of BOT, 28 patients with the morphologically confirmed diagnosis of this pathology were investigated
Bilateral process was stated in 8 (27,6